PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA ORGANISASI SMA NEGERI 3 SALATIGA (STUDI KASUS ORGANISASI OSIS SMA NEGERI 3 SALATIGA) - Candra Christian (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Within the organization there must be a leader who is responsible for the organization as a whole, the leader has a different leadership style. Leadership style of a leader can affect its members, especially the work motivation of members in the organization. In this study, the aim is to determine the effect of leadership style on organizational work motivation. This research approach uses a quantitative approach. The locus of this research is in SMA N 3 Salatiga. The population of this research is the Organization in SMA N 3 Salatiga, while the sample used is the Osis Organization SMA N 3 Salatiga. Data collection using a questionnaire with a number of respondents 50 people who are members of the Osis. The results found that the influence of leadership style on work motivation was 40.6% while 59.4% was influenced by other factors. While the results of the calculation of t arithmetic shows the value of t arithmetic greater than t table (5.733> 2.01063) so that Ho is rejected and Ha is accepted. Means the independent variable (Leadership Style) has a significant influence on the dependent variable (Work Motivation).